(untitled) (مجلة إحالات, 2026)
Assessment is one of the most important variables that play a decisive role in improving the quality of teaching and learning. The present study was designed to investigate the quality of assessment methods within ESP instructors as well as the major challenges they face throughout their teaching process at the chemistry department, University of Tlemcen (Algeria). Results revealed that ESP instructors depend on traditional methods to a large extent. Besides, they encounter challenges as they need to improvise since they lack adequate training. Moreover, students seemed to have some difficulties in assessment tasks as they lacked the necessary skills to communicate in the language in context.